Constitutive and conditional gene knockout mice for the study of intervertebral disc degeneration: Current status, decision considerations, and future possibilities - Ze‐Yu Lu; Peng‐Bo Chen; Qing‐Yin Xu; Bo Li; Sheng‐Dan Jiang; Lei‐Sheng Jiang; Xin‐Feng Zheng (JOR Spine, 2023)
Abstract There have been an increasing number of patients with degenerative disc diseases due to the aging population. In light of this, studies on the pathogenesis of intervertebral disc degeneration have become a hot topic, and gene knockout mice have become a valuable tool in this field of research. With the development of science and technology, constitutive gene knockout mice can be constructed using homologous recombination, zinc finger nuclease, transcription activator‐like effector nuclease technology and clustered regularly interspaced short palindromic repeats/Cas9 (CRISPR/Cas9) system, and conditional gene knockout mice can be constructed using the Cre/LoxP system. The gene‐edited mice using these techniques have been widely used in the studies on disc degeneration. This paper reviews the development process and principles of these technologies, functions of the edited genes in disc degeneration, advantages, and disadvantages of different methods and possible targets of the specific Cre recombinase in intervertebral discs. Recommendations for the choice of suitable gene‐edited model mice are presented. At the same time, possible technological improvements in the future are also discussed.